2016
DOI: 10.1103/physrevb.94.024301
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast optical response of the amorphous and crystalline states of the phase change materialGe2Sb2Te5

Abstract: We examine the ultrafast optical response of the crystalline and amorphous phases of the phase change material Ge2Sb2Te5 below the phase transformation threshold. Simultaneous measurement of the transmissivity and reflectivity of thin film samples yields the time-dependent evolution of the dielectric function for both phases. We then identify how lattice motion and electronic excitation manifest in the dielectric response. The dielectric response of both phases is large but markedly different. At 800 nm, the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…In support of our hypothesis that light affects phase transitions in other ways than thermally, recent experiments have attributed photoinduced phase transitions to electronic excitation at subnanosecond timescales . It has also been reported that photoinduced crystallization of amorphous selenium films is polarization dependent .…”
supporting
confidence: 84%
“…In support of our hypothesis that light affects phase transitions in other ways than thermally, recent experiments have attributed photoinduced phase transitions to electronic excitation at subnanosecond timescales . It has also been reported that photoinduced crystallization of amorphous selenium films is polarization dependent .…”
supporting
confidence: 84%
“…The emergent mode at 3.6 THz is considered to be the A 1 mode of tellurium (Te) [30][31][32][33][34] due to segregation of atomic Te from the MoTe 2 samples as a result of surface melting induced by heat-accumulation effects of high repetitive pulsed laser irradiation. The Te segregation observed to date in coherent phonon spectra appearing at 3.6 THz has been occasionally observed in other telluride compounds, such as Ge 2 Sb 2 Te 5 [35], Sb 2 Te 3 [36,37], CdTe [38], ZnTe [39] as well as static-measurement studies on MoTe 2 [18]. On the other hand, additional phonon modes related to the different structural phases were not observed after the laser irradiation: the 2H-to-1T' and 1T'-to-2H phase transitions were not observed.…”
Section: Resultsmentioning
confidence: 55%
“…Miller et al. [ 21 ] obtained the similar tendencies and timescales for optical excitation of Ge 2 Sb 2 Te 5 , this alloy being also a prototypical PCM. The variation of the pump fluence has no effect on the recorded transients of ε r .…”
Section: Resultsmentioning
confidence: 73%